The Nahdlatul Ulama Paradigm in Legal Fatwa on Non- Muslim Citizenship - Syakur, Muhammad -; Nashihin, Husna (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The 2019 NU (Nahdlatul Ulama) National Conference/Consultation in Banjar, West Java, decided not to categorize non-Muslims in the public context as mu'āhad, musta'man, żimmy, or harbi. The status of non-Muslims in a nation-state is as citizens (muwathin) who have equal rights and obligations as other citizens. This decision has opened up new discourse on the legal decision-making methodology in NU, which needs to be studied. The research method uses two approaches: first, usul fiqh with the theory of fatwa change (at-taghayyur fī al-fatwa); second, a scientific approach with the theory of methodology of scientific research programs by Imre Lakatos. The NU paradigm of protecting the primary sources of Islam through the mechanism of fatwa change is a key finding of the researcher. The primary sources of Islam being protected are the universal values contained in the sacred texts (the Qur'an), which are manifested in the usūl al-khamsah (five fundamental principles): hifzh ad-dīn (preserving religion), hifzh al-nafs wa al-‘irdh (preserving life and honor), hifzh al-‘aql (preserving intellect), hifzh al-nasl (preserving lineage), and hifzh al-māl (preserving property).